2019
DOI: 10.4236/tel.2019.94074
|View full text |Cite
|
Sign up to set email alerts
|

A Move towards Cashless Economy: A Case of Continuous Usage of Mobile Wallets in India

Abstract: Purpose: India is trying to move from cash-dominant economy to cashless economy using digital technologies namely mobile wallets and digital money. A large number of companies have launched their mobile wallet services and people have also rapidly adopted of mobile wallets. However, there is lot of user switching among mobile wallets of different service providers. In such a scenario, it becomes imperative for the mobile wallet service providers to understand the quality factors that support continuous intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
1
23
1
Order By: Relevance
“…Usefulness can function as a benchmark for the number and variety of applications used so that the implications of this condition lead to many user preferences in trying similar E-Wallet applications (Setiani, 2018). On the other hand, the results of this study contradict some previous studies (Aksami dan Jember, 2019); (Routray et al 2019) & (Kumala, Pranata, and Thio 2020), which showed that the usefulness aspect has a positive and significant effect on interest in using E-Wallet services. This means that if the usefulness obtained is high, the interest in using E-Wallet services will increase, thus increasing non-cash financial transactions (Kevin Anarjia 2018).…”
Section: The Effect Of Perceived Usefulness On Behavioral Intentioncontrasting
confidence: 99%
“…Usefulness can function as a benchmark for the number and variety of applications used so that the implications of this condition lead to many user preferences in trying similar E-Wallet applications (Setiani, 2018). On the other hand, the results of this study contradict some previous studies (Aksami dan Jember, 2019); (Routray et al 2019) & (Kumala, Pranata, and Thio 2020), which showed that the usefulness aspect has a positive and significant effect on interest in using E-Wallet services. This means that if the usefulness obtained is high, the interest in using E-Wallet services will increase, thus increasing non-cash financial transactions (Kevin Anarjia 2018).…”
Section: The Effect Of Perceived Usefulness On Behavioral Intentioncontrasting
confidence: 99%
“…Recent study concluded that PU positively influences that attitude and intentions of users in mobile wallet context (Chawla and Joshi, 2019). In this view, earlier studies posited that the intention to use mobile payment services is positively influenced by PU (Routray et al, 2019;Routray, 2019;Pertiwi et al, 2020;Jin, 2020). Hence, based on these arguments, it can be hypothesized that: H1.…”
Section: Theoretical Background and Development Of Hypothesesmentioning
confidence: 94%
“…The technology adoption literature sometimes refers to this as previous experience with the technology, but in other cases, it is also known as continuous use intention (cf. Daragmeh et al, 2021;Routray et al, 2019). We determined that the user's status could significantly impact the relationship between the antecedents and the intention to use eWallets.…”
Section: Moderators Of the Importance Of The Utaut Antecedentsmentioning
confidence: 99%